A Changing Role for the Arboretum of the Universidad Austral de Chile (UACH) - Hechenleitner Vega, Paulina (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2005)
The Arboretum of Universidad Austral de Chile is playing an important role in cultivating some of Chile’s most threatened woody plant species in order to establish ex situ conservation collections for research, education and to assist the restoration of depleted wild populations. Changing the way in which the Arboretum manages its plant collections, so that it can play a more effective role in conservation, has been an important output of a Darwin Initiative funded project run in collaboration with the Royal Botanic Garden Edinburgh. The three year project, ’An Integrated Programme for the Conservation of Chilean Threatened Endemic Plants’ was started in 2002. This paper describes how the project has assisted in developing facilities in the Arboretum to propagate and grow some of Chile’s most threatened plant species and includes details of six lesser known, threatened narrow endemics.